Badania nad stylem dydaktycznym w Polsce - Nocoń, Jolanta (Stylistyka, 2021)
The article discusses main trends in didactic style research in Poland in a selective and synthetic manner. The first part of the text is of a theoretical character; it focuses on the status of didactic style compared to other functional variant of the Polish language. On the other hand, the overview part includes two perspectives on the description of Polish didactic style research output; namely the object perspective (i.e. what is studied) and the methodological perspective (i.e. how it is studied). This part discusses research within the following stylistic paradigms: functional, pragmatic, textual and discursive. The overview is completed with a presentation of selected works of a pedagogie and psychological orientation. The finał part of the article indicates some of the needs of and perspectives on didactic style research, for instance those offered by such research methodologies as Critical Discourse Analysis or cognitivism.